Exploring the Relationship between Principal Leadership Styles and Teacher Work Discipline - Nurfaisal, Nurfaisal; Asfar, Ali; Sunengko, Sunengko (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research explores the relationship between the school principal's leadership style and teachers' work discipline in State Senior High Schools Pekanbaru, Riau. The study adopts a quantitative approach with a survey method and correlation technique. Through random sampling, the research involves 40 teachers from eleven State Senior High Schools in Pekanbaru. Data collection is conducted using a questionnaire, which has been calibrated with validity testing using Pearson Product Moment and reliability coefficient with Cronbach's Alpha formula. The research results indicate a relationship between the leadership style of school principals and the discipline of teachers in State Senior High Schools in Pekanbaru. The significance testing of a correlation coefficient of 0.51 supports this relationship. It suggests a moderate connection between the principal's leadership style and teacher discipline. This study implies that enhancing teacher discipline can be achieved through the role of the school principal's leadership style. In other words, a correlation of 0.51 indicates that the principal's role in leading and guiding teachers can have a positive impact on their work discipline, and these efforts may be crucial in achieving a higher quality of education.